Pengaruh Gratis Ongkos Kirim, Diskon Dan Online Customer Review Terhadap Keputusan Pembelian Konsumen TikTok Shop (Studi Pada Mahasiswa FEB Angkatan 2019 Universitas Islam - Ahmad Faisal Hakim; N Rachma; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the effect of free shipping, discounts and online customer reviews on purchasing decisions of consumers of the TikTok Shop study on Students of the Faculty of Economics and Business class of 2019, Islamic University of Malang. The type of research used is explanatory research with a quantitative approach. The research sample was taken by purposive sampling technique with the Malhotra formula used to take the sample, namely the number of items x 5 so that the total sample is 85 respondents. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Uji F) and testing the partial hypothesis (Uji t). The results of his research show that free shipping has a significant and positive influence on the purchasing decisions of TikTok Shop consumers, discounts have a significant and positive influence on the purchasing decisions of TikTok Shop consumers and online customer reviews partially have no effect on the purchasing decisions of TikTok Shop consumers. In addition, simultaneously free shipping, discounts and online customer reviews on purchasing decisions of TikTok Shop consumers. Keywords: Free Shipping, Discounts and Online Customer Reviews and Consumer Purchase Decisions TikTok Shop.